López Herrerías, JA. (2001). Educación para la nueva Psíco-Cultura. Rehacer la educación y la escuela del nuevo milenio desde la Generación deI 98. - José Mª Quintana Cabanas (Universidad Complutense de Madrid, 2001)
Sin resumen